International Trade and Labor Market Discrimination - Richard Chisik; Julian Emami Namini (Tinbergen Institute, 2016)
We embed a competitive search model with labor market discrimination, or nepotism, into a two-sector, two-country framework in order to analyze how labor market discrimination impacts the pattern of international trade and also how trade trade affects discrimination. Discrimination, or nepotism, reduces the matching probability and output in the skilled-labor intensive differentiated-product sector so that the country with more discriminatory firms has a comparative advantage in the simple sector. As countries alter their production mix in accordance with their comparative advantage, trade liberalization can then reinforce the negative effect of discrimination on development in the more discriminatory country and reduce its effect in the country with fewer discriminatory firms. Similarly, the profit difference between non-discriminatory and discriminatory firms increases in the less discriminatory country and shrinks in the more discriminatory one. In this way trade can further reduce discrimination in a country where it is less prevalent and increase it where it is more firmly entrenched.
Keywords: F16; F66; J71; 330; Discrimination; Nepotism; International Trade; Competitive Search